2016
DOI: 10.1177/1933719115612133
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Prevents Menopausal Syndromes in Ovariectomized Mouse

Abstract: Cysteine (Cys) is well known to be involved in oxidation-reduction reactions, serving as a source of sulfides in the body. Amino acids are known to improve menopausal symptoms and significantly reduce morbidity. This study aims to find an unrevealed effect of Cys with estrogenic and osteogenic actions. Ovariectomized (OVX) mice were treated with Cys daily for 8 weeks. Estrogen-related and osteoporosis-related factors were analyzed in the vagina, serum, and tibia. Cys was treated in estrogen receptor (ER)-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Also, recent metabolomics studies reported that the amino acids including glutamine [ 8 ], tryptophan [ 9 ], and cystine [ 10 ] were associated with BMD in postmenopausal women of East Asian. Of these identified BMD-related amino acids in our study, GABA [ 28 ], cysteine [ 29 ], taurine [ 30 ], and glutamic acid [ 31 ] have shown some evidence for their potential roles in bone metabolism by in vitro and/or in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, recent metabolomics studies reported that the amino acids including glutamine [ 8 ], tryptophan [ 9 ], and cystine [ 10 ] were associated with BMD in postmenopausal women of East Asian. Of these identified BMD-related amino acids in our study, GABA [ 28 ], cysteine [ 29 ], taurine [ 30 ], and glutamic acid [ 31 ] have shown some evidence for their potential roles in bone metabolism by in vitro and/or in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“…It is an important source of sulfur in human metabolism. In ovariectomized (OVX) mice, cysteine administration improved BMD and other menopausal symptoms [ 29 ]. N-acetyl cysteine, a derivative of cysteine, can function as an osteogenesis-enhancing molecule to accelerate bone regeneration by activating differentiation of osteogenic lineages [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anpep, also known as aminopeptidase N or CD13, constitutes a multifunctional membrane-bound zincdependent metalloprotease that is ubiquitously conserved in renal, intestinal, placental, brain, and hepatic tissues and is also expressed on monocytes and myeloid progenitor cells (Dringen et al, 2001;Rawlings et al, 2006). Upon degradation by Anpep, cysteine participates in oxidation-reduction reactions, providing sulfides in the body to regulate proliferation, ERβ mRNA expression, and estrogen response element activity (Han et al, 2016). Taurine, which is further catalyzed from Cys by cysteine sulfinic acid decarboxylase, exerts an effect as an inhibitory neurotransmitter on the central nervous system (Renteria et al, 2004;Kim and Kim, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The ovariectomy in the rat induces permanent anoestrus, but it is not similar to the human physiological menopause. This experimental model plays an important role in understanding the pathophysiological modifications of the anoestrus syndrome, thus helping in the development of multiple adjuvant therapies [5,12].…”
Section: Introductionmentioning
confidence: 99%